O acesso de transexuais e travestis à educação superior - TATIANE DA SILVA LIMA (2023)
This thesis aims to investigate the strategies engendered by the State, by the transsexual and transvestite movements and by the federal universities to promote the access of transsexuals and transvestites to higher education in Brazil, in the period from 2003 to 2016, whose specific objectives are to contextualize the conditions social, historical and political factors that interfere in the access of transsexuals and transvestites to higher education; explore the democratization of access to higher education during the governments of Luiz Inácio Lula da Silva (2003 - 2010) and Dilma Rousseff (2011 - 2016); and analyze how these strategies were instituted to democratize access for transsexuals and transvestites to higher education. Therefore, under the precepts of historical-dialectical materialism, but focusing on Nancy Fraser's theory of social justice, the present work was developed through documental and bibliographical research, having as source academic productions and news that express the social context. history of transsexuals and transvestites, higher education policies, guiding documents, normative acts that mention this group in education, and quantitative data on those enrolled who request the use of their social name to take the National Teaching Examination Medium (ENEM). As a result, it should be noted that the strategies developed refer to positive visibility, trans courses, quantitative research, regulation of the social name in ENEM and quotas in public universities. Independent and joint, these strategies are affirmative measures that start from the recognition of identities and that can contribute to the democratization of access for this group. However, its own urgency and realization also denotes the discriminatory and excluding nature of socio-historical, maternal, political and educational conditions in Brazil, whose measures are not yet sufficient to include and benefit everyone, just as they do not tend towards transformation. structures that give rise to unequal conditions of access.